Cover Picture: Identification of N‐Arylated NH125 Analogues as Rapid Eradicating Agents against MRSA Persister Cells and Potent Biofilm Killers of Gram‐Positive Pathogens (ChemBioChem 4/2017). (31st January 2017) - Abouelhassan, Yasmeen; Basak, Akash; Yousaf, Hussain; Huigens, Robert W.
Abstract : The cover picture shows the destruction of a bacterial membrane by a new NH125 analogue. Through chemical synthesis and biological evaluation, the authors have identified potent N‐arylated compounds that rapidly kill MRSA persister cells (99.99 % in 30 minutes) and eradicate surface‐attached bacterial biofilms of multiple Gram‐positive pathogens through the destructive lysis of bacterial membranes. These N‐arylated NH125 analogues demonstrated enhanced activity in killing persister cells and eradicating biofilm when tested alongside a structurally diverse panel of membrane‐active agents. More information can be found in the communication by R. W. Huigens III et al. onpage 352 in Issue 4, 2017 (DOI:10.1002/cbic.201600622 ).